Age-Dependent Effects of Haptoglobin Deletion in Neurobehavioral and Anatomical Outcomes Following Traumatic Brain Injury - Glushakov, Alexander V.; Arias, Rodrigo A.; Tolosano, Emanuela; Doré, Sylvain (Frontiers in Molecular Biosciences, 2016)
Cerebral hemorrhages are common features of traumatic brain injury (TBI) and their presence is associated with chronic disabilities. Recent clinical and experimental evidence suggests that haptoglobin (Hp), an endogenous hemoglobin-binding protein most abundant in blood plasma, is involved in the intrinsic molecular defensive mechanism, though its role in TBI is poorly understood. The aim of this study was to investigate the effects of Hp deletion on the anatomical and behavioral outcomes in the controlled cortical impact model using wild type (WT) C57BL/6 mice and genetically modified mice lacking the Hp gene (Hp-/-) in two age cohorts [2–4 mo old (young adult) and 7–8 mo old (older adult)]. The data obtained suggest age-dependent significant effects on the behavioral and anatomical TBI outcomes and recovery from the injury. Moreover, in the adult cohort, neurological deficits of Hp-/- mice at 24 h were significantly improved as compared to WT; whereas there were no significant differences in brain pathology between these genotypes. In contrast, in the older adult cohort, Hp-/- mice had significantly larger lesion volumes compared to WT, but neurological deficits were not significantly different. Immunohistochemistry for ionized calcium-binding adapter molecule 1 (Iba1) and glial fibrillary acidic protein (GFAP) revealed significant differences in microglial and astrocytic reactivity between Hp-/- and WT in selected brain regions of the adult but not the older adult age cohort. In conclusion, the data obtained in the study provide clarification on the age-dependent aspects of the intrinsic defensive mechanisms involving Hp that might be involved in complex pathways differentially affecting acute brain trauma outcomes.